2021
DOI: 10.3892/etm.2021.10358
|View full text |Cite
|
Sign up to set email alerts
|

Role of m6A in osteoporosis, arthritis and osteosarcoma (Review)

Abstract: RNA modification is a type of post-transcriptional modification that regulates important cellular pathways, such as the processing and metabolism of RNA. The most abundant form of methylation modification is RNA N6-methyladenine (m6A), which plays various post-transcriptional regulatory roles in cellular biological functions, including cell differentiation, embryonic development and disease occurrence. Bones play a pivotal role in the skeletal system as they support and protect muscles and other organs, facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 196 publications
(243 reference statements)
0
14
0
Order By: Relevance
“…52,54 METTL3 is the key m 6 A writer that has been implicated in the pathogenesis and development of bone-related diseases including osteoporosis, arthritis and osteosarcoma. 55 However, controversy exists regarding the expression of METTL3 and occurrence and development of osteoporosis. For instance, one study reported that disruption of METTL3 in mice destroyed bone formation, impaired osteogenic differentiation and improved marrow adiposity whereas overexpression of METTL3 in BMMSCs protected mice against osteoporosis caused by estrogen deficiency.…”
Section: Relative Protein Expressionmentioning
confidence: 99%
“…52,54 METTL3 is the key m 6 A writer that has been implicated in the pathogenesis and development of bone-related diseases including osteoporosis, arthritis and osteosarcoma. 55 However, controversy exists regarding the expression of METTL3 and occurrence and development of osteoporosis. For instance, one study reported that disruption of METTL3 in mice destroyed bone formation, impaired osteogenic differentiation and improved marrow adiposity whereas overexpression of METTL3 in BMMSCs protected mice against osteoporosis caused by estrogen deficiency.…”
Section: Relative Protein Expressionmentioning
confidence: 99%
“…m6A modification is closely related to the occurrence and development of cancer and participates in cell differentiation, proliferation, migration, immunity, and drug resistance. Deregulation of m6A regulators in OS is inevitable [ 11 , 13 , 30 , 31 ]. Miao et al reported that METTL3 contributes to proliferation, migration, and invasion of OS cells and activates the Wnt/β-catenin signaling pathway by regulating m6A modification of LEF1 mRNAs [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bone development and remodeling require precise regulation of gene expression through epigenetics, including RNA modifications. M6A plays an important role in the development and metabolism of bone [ 13 , 14 ]. It affects various bone diseases, such as OP, bone tumors, and arthritis [ 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…M6A plays an important role in the development and metabolism of bone [ 13 , 14 ]. It affects various bone diseases, such as OP, bone tumors, and arthritis [ 13 , 15 ]. BMSCs maintain a balance between osteogenic and adipogenic differentiation to maintain bone health.…”
Section: Discussionmentioning
confidence: 99%